Estudio de la dinámica y función de la proteína heterocromática 1 (HP1y) durante el proceso de miogénesis - Charó, Nancy Lorena (2015)
In a previous study we show that upon induction of 3T3-L1 preadipocytes differentiation, the nuclear non-histone protein the HP1y transiently concentrates in the nuclear pole opposite to the MTOC. Then, we investigated whether HP1y nuclear polarization occurred in other processes of cell differentiation, and for this we analyzed the subcellular distribution of HP1y during myogenesis. Using indirect immunofluorescence and confocal microscopy we observed that in C2C12 myoblasts, HP1y, a protein so far described only in the nucleus, besides being located in euchromatic and heterochromatic nuclear regions as already reported (Minc et al., 1999; Minc et al., 2000), remarkably localizes in the cytoplasm. Four days post-induction of differentiation, myoblasts become myotubes where HP1y localized predominantly in the cytoplasm exhibiting a filamentous pattern longitudinally arranged. On the contrary, HP1a, another member of the HP1 family, is present in the nucleus of both myoblasts and myotubes. Western blot analysis of nuclear and cytoplasmic fractions of myoblasts and myotubes showed that HP1y is present in both fractions. In mature myotubes and myofibrils isolated from muscle of mice´s limbs HP1y also localizes in the cytoplasm but in transversal filaments. According to HP1y filamentous aspect observed in myotubes, we explored the possible association with proteins of the cytoskeleton, and surprisingly we found that HP1y interacts with actin and tubulin. Finally, to investigate the functional importance of HP1y during myogenesis, C2C12 myoblasts were generated in which the expression of HP1y was stably interfered using shRNA. The C2C12HP1y- are unable to differentiate or give rise to thin myotubes. In summary, HP1y is not exclusively localized in the nucleus and it is required for the proper generation of the myotubes.